(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2023)
This article aims to analyze the appropriations of the podcast media as a means of communication in the context of contemporary women’s emancipatory struggles. Specifically, what we want to understand is whether the messages conveyed by the Olhares Podcast contribute to broaden the struggle of feminist listeners in cyberspace, empowering and mobilizing women. The research anchors its theoretical approach in authors such as Castells (2013, 2017), Cremades (2009), Alvarez (2014) and Costa (2018). This is a case study that uses netnography techniques combined with data collection based on interviews with listeners and the program’s producer. The netnographic approach is present due to the weight of the online component of the object of study. The research points to the potential of the podcast as a medium for the engagement, empowerment and training of women, mainly in line with other strategies that use the mobilizing force of personal reports as a connection engine between women.